2015
DOI: 10.1093/bja/aeu333
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, triple-masked, active-controlled investigation of the relative effects of dose, concentration, and infusion rate for continuous popliteal-sciatic nerve blocks in volunteers

Abstract: NCT01898689.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…32 This would explain why a previous study reported a larger cephalad-caudad cutaneous effect with the use of a 0.6 mL/kg bolus of levobupivacaine 0.125% compared with a bolus of half this volume—it was not the higher volume but rather the higher dose responsible for the differing results. 16 While the current investigation did compare repeated large (24 mL) bolus volumes with a steady basal infusion of 8 mL/h, the mass of ropivacaine administered was equivalent at Hours 3 and 6.…”
Section: Discussionmentioning
confidence: 98%
“…32 This would explain why a previous study reported a larger cephalad-caudad cutaneous effect with the use of a 0.6 mL/kg bolus of levobupivacaine 0.125% compared with a bolus of half this volume—it was not the higher volume but rather the higher dose responsible for the differing results. 16 While the current investigation did compare repeated large (24 mL) bolus volumes with a steady basal infusion of 8 mL/h, the mass of ropivacaine administered was equivalent at Hours 3 and 6.…”
Section: Discussionmentioning
confidence: 98%
“…19 In our institutional pilot data, administration of 15-ml boluses of 0.5% ropivacaine in the adductor canal at 6-h intervals (total dose 300 mg in 24 h) resulted in satisfactory pain relief after arthroscopic ACL surgery. 20 Given that the block effect depended on the local anaesthetic dose, 21 we selected an identical total dose of 300 mg of ropivacaine to be delivered in 24 h in each group. A higher concentration of local anaesthetic at a lower infusion rate was demonstrated to be as effective as a lower concentration of local anaesthetic administered at higher infusion rates.…”
Section: Discussionmentioning
confidence: 99%
“…A higher concentration of local anaesthetic at a lower infusion rate was demonstrated to be as effective as a lower concentration of local anaesthetic administered at higher infusion rates. 20 Given that the block effect depended on the local anaesthetic dose, 21 we selected an identical total dose of 300 mg of ropivacaine to be delivered in 24 h in each group. Accordingly, an infusion of 12.5 mg/h or 2.5 ml/h of 0.5% ropivacaine was calculated for administration in the continuous group.…”
Section: Discussionmentioning
confidence: 99%
“…163,164 Relatedly, providing local anesthetic as automatic, repeated bolus doses does not change block effects compared with a continuous basal infusion, as long as the total dose remains constant. 156,165,166 Similarly, no additive has demonstrated improved analgesia and/or decreased motor block, including epinephrine [167][168][169] and clonidine. [170][171][172] One of the most promising fall-reduction interventions is converting continuous femoral to adductor canal nerve blocks, owing to the demonstrated reduction of induced quadriceps weakness.…”
Section: Ketaminementioning
confidence: 99%